Optimizing Potassium Fertilization for Precision Nutrition: Effects on Growth, Physiology, and Seed Potassium Content of Two Soybean Varieties - Ratu Fatkhunnisa; Supijatno Supijatno; Edi Santosa (Journal of Tropical Crop Science, 2026)
Potassium is an essential macronutrient that supports major physiological processes in plants and strongly influences soybean productivity. This study aimed to evaluate the effects of different potassium fertilization levels on plant physiology, yield performance, and seed nutritional composition in two soybean varieties, ‘Dena 1’ and ‘Denasa 1’.The research employed a factorial completely randomized group design with five potassium fertilizer levels (0, 15, 30, 45, and 60 kg K2O/ha) and two soybean varieties (‘Dena 1’ and ‘Denasa 1’), with three replications. The results showed that the potassium dose significantly affected plant height and leaf number but did not influence photosynthetic rate or stomatal conductance. The ‘Dena 1’ variety exhibited better growth, greater leaf greenness, and faster generative development than ‘Denasa 1’. The optimal potassium dose of 45 kg/ha improved yield components, resulting in a 30.7% increase in seed weight and a 45.8% increase in the number of filled pods compared with the control. A positive correlation was found between plant potassium content and key physiological traits, such as photosynthesis and transpiration rates. Seed nutrition analysis showed that soybean varieties significantly influenced nitrogen and phosphorus levels at the R7 and R8 stages, whereas the potassium fertilization dose had no significant effect on seed nutrient concentrations. Nutrient levels increased from R6 to R7 before declining at R8, reflecting nutrient redistribution during seed filling. Overall, the results suggest that applying 45 kg K2 O/ha is an effective fertilization rate for enhancing soybean physiological performance and yield, while varietal characteristics remain the primary factor shaping seed nutritional composition.